FROM ACTIVITY-BASED WORKPLACES TO PUBLIC EMPLOYEE PERFORMANCE: DIGITALIZATION AS THE MEDIATING MECHANISM - Hermansyah, Verdy Prahutri; Mulyanti, Rita Yuni; Suhana, Suhana (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Activity-based workplaces (ABW) are increasingly used to support flexible work, yet their contribution to employee performance remains inconsistent, particularly in public organizations where work must remain standardized, traceable, and accountable. This study examines whether workplace digitalization explains the translation of ABW into public employee performance. Method: A quantitative explanatory-causal design was used with cross-sectional survey data from 63 functional public procurement officers selected through purposive sampling from a target population of 66 officers. Responses were measured on a six-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4. Results: ABW has a strong positive effect on digitalization (β = 0.763; p < 0.001), and digitalization positively affects employee performance (β = 0.411; p = 0.014). The direct ABW → employee performance effect is negative and not significant (β = -0.408; p = 0.130), whereas the indirect ABW → digitalization → performance effect is positive and significant (β = 0.313; p = 0.012), indicating indirect-only mediation. Discussion/Novelty and Implication: The study shows that ABW does not generate performance value solely through spatial flexibility; its contribution emerges when flexible space is converted into digitally enabled access, coordination, and execution of work. Public organizations should therefore treat ABW and digitalization as an integrated work-system intervention by strengthening reliable digital infrastructure, standardized digital workflows, leadership support, and employee digital capability.